Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To find the value of [tex]\(\frac{8^y}{4^x}\)[/tex] given the equation [tex]\(2x - 3y = 3\)[/tex], follow these steps:
1. Express [tex]\(y\)[/tex] in terms of [tex]\(x\)[/tex]:
Given the equation:
[tex]\[ 2x - 3y = 3, \][/tex]
we solve for [tex]\(y\)[/tex]:
[tex]\[ 2x - 3y = 3 \quad \Rightarrow \quad -3y = 3 - 2x \quad \Rightarrow \quad y = \frac{2x - 3}{3}. \][/tex]
2. Substitute [tex]\(y\)[/tex] into [tex]\(\frac{8^y}{4^x}\)[/tex]:
We know:
[tex]\[ y = \frac{2x - 3}{3}. \][/tex]
First, recall the properties of exponents:
[tex]\[ 8 = 2^3 \quad \text{and} \quad 4 = 2^2. \][/tex]
So,
[tex]\[ 8^y = (2^3)^y = 2^{3y} \quad \text{and} \quad 4^x = (2^2)^x = 2^{2x}. \][/tex]
Thus,
[tex]\[ \frac{8^y}{4^x} = \frac{2^{3y}}{2^{2x}} = 2^{3y - 2x}. \][/tex]
3. Substitute [tex]\(y = \frac{2x - 3}{3}\)[/tex] into the exponent:
Substitute [tex]\(y\)[/tex] in [tex]\(2^{3y - 2x}\)[/tex]:
[tex]\[ 3y = 3 \left(\frac{2x - 3}{3}\right) = 2x - 3. \][/tex]
Therefore:
[tex]\[ 3y - 2x = (2x - 3) - 2x = -3. \][/tex]
Hence,
[tex]\[ 2^{3y - 2x} = 2^{-3}. \][/tex]
4. Calculate the value:
Since,
[tex]\[ 2^{-3} = \frac{1}{2^3} = \frac{1}{8}. \][/tex]
Thus, the value of [tex]\(\frac{8^y}{4^x}\)[/tex] given the equation [tex]\(2x - 3y = 3\)[/tex] is [tex]\(\boxed{\frac{1}{8}}\)[/tex].
1. Express [tex]\(y\)[/tex] in terms of [tex]\(x\)[/tex]:
Given the equation:
[tex]\[ 2x - 3y = 3, \][/tex]
we solve for [tex]\(y\)[/tex]:
[tex]\[ 2x - 3y = 3 \quad \Rightarrow \quad -3y = 3 - 2x \quad \Rightarrow \quad y = \frac{2x - 3}{3}. \][/tex]
2. Substitute [tex]\(y\)[/tex] into [tex]\(\frac{8^y}{4^x}\)[/tex]:
We know:
[tex]\[ y = \frac{2x - 3}{3}. \][/tex]
First, recall the properties of exponents:
[tex]\[ 8 = 2^3 \quad \text{and} \quad 4 = 2^2. \][/tex]
So,
[tex]\[ 8^y = (2^3)^y = 2^{3y} \quad \text{and} \quad 4^x = (2^2)^x = 2^{2x}. \][/tex]
Thus,
[tex]\[ \frac{8^y}{4^x} = \frac{2^{3y}}{2^{2x}} = 2^{3y - 2x}. \][/tex]
3. Substitute [tex]\(y = \frac{2x - 3}{3}\)[/tex] into the exponent:
Substitute [tex]\(y\)[/tex] in [tex]\(2^{3y - 2x}\)[/tex]:
[tex]\[ 3y = 3 \left(\frac{2x - 3}{3}\right) = 2x - 3. \][/tex]
Therefore:
[tex]\[ 3y - 2x = (2x - 3) - 2x = -3. \][/tex]
Hence,
[tex]\[ 2^{3y - 2x} = 2^{-3}. \][/tex]
4. Calculate the value:
Since,
[tex]\[ 2^{-3} = \frac{1}{2^3} = \frac{1}{8}. \][/tex]
Thus, the value of [tex]\(\frac{8^y}{4^x}\)[/tex] given the equation [tex]\(2x - 3y = 3\)[/tex] is [tex]\(\boxed{\frac{1}{8}}\)[/tex].
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.